2011
DOI: 10.1128/jvi.05512-11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Human Coronavirus OC43 Reveals Evolution of Different Genotypes over Time and Recent Emergence of a Novel Genotype due to Natural Recombination

Abstract: Although human coronavirus OC43-OC43 (HCoV-OC43Coronaviruses cause infections in a wide variety of animals, resulting in respiratory, enteric, hepatic, and neurological diseases of various levels of severity. Based on genotypic and serological characterization, coronaviruses traditionally were classified into three distinct groups, groups 1, 2, and 3 (4). Recently, the Coronavirus Study Group of the International Committee for Taxonomy of Viruses has renamed the traditional group 1, 2, and 3 coronaviruses as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
279
4
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 240 publications
(320 citation statements)
references
References 60 publications
33
279
4
4
Order By: Relevance
“…human in the 1890s. 57 The more recent example of interspecies transmission was the jumping of the lineage B betacoronavirus SARS-CoV from bats to civets and then to humans which caused the SARS epidemic in 2003. 11,19,58e62 Though the seroprevalence of anti-HCoV-EMC antibody found no indication of positivity among residents in the Kingdom of Saudi Arabia, their demographic details, particularly the history of animal exposure, were not described.…”
Section: Discussionmentioning
confidence: 99%
“…human in the 1890s. 57 The more recent example of interspecies transmission was the jumping of the lineage B betacoronavirus SARS-CoV from bats to civets and then to humans which caused the SARS epidemic in 2003. 11,19,58e62 Though the seroprevalence of anti-HCoV-EMC antibody found no indication of positivity among residents in the Kingdom of Saudi Arabia, their demographic details, particularly the history of animal exposure, were not described.…”
Section: Discussionmentioning
confidence: 99%
“…Divergence time was calculated on the basis of RdRp gene sequence data by using a Bayesian Markov Chain Monte Carlo approach as implemented in BEAST version 1.8.0 (http://beast.bio.ed.ac.uk), as described ( 15 , 19 , 29 , 30 ). Bayesian skyline under a relaxed-clock model with an uncorrelated exponential distribution was adopted for making inferences because Bayes factor analysis for the RdRp gene indicated that this model fitted the data better than other models tested.…”
Section: Methodsmentioning
confidence: 99%
“…Bootscan analysis was also used to detect possible recombination using the nucleotide alignment of the S gene sequences of virus species in Betacoronaviruses 1 and also CRCoV. Bootscan analysis was performed using Simplot version 3.5.1 as described previously (Lau et al, 2011;Woo et al, 2006), with BCoV, HCoV, ECoV, PHEV and CRCoV strains as the query.…”
Section: Methodsmentioning
confidence: 99%